Krisis Kesiapan Nikah Gen Z Dalam Narasi “Pernikahan Itu Menakutkan”: Relevansi Hukum Keluarga Islam Di Era Digital - Farhan Lutfi, Farhan Lutfi (Institut Agama Islam Negeri Metro, 2025)
The growing Marriage is Scary phenomenon among Generation Z reflects a paradigm shift in perceptions of marriage—from a symbol of maturity to a source of emotional anxiety, uncertainty about the future, and economic burden. This study analyzes the marriage readiness of Gen Z from the perspective of Islamic law by examining Articles 15–17 of the Compilation of Islamic Law (Kompilasi Hukum Islam, KHI) as a normative foundation. Employing a qualitative juridical-normative method with a critical-narrative analysis approach, the study draws on legal texts, academic literature, and secondary sources such as media articles, survey reports, and digital content that illustrate Gen Z’s socio-cultural dynamics. The findings reveal a gap between the normative expectations of marriage readiness in the KHI and the actual sociocultural realities faced by Gen Z, particularly in terms of psychosocial readiness and power relations within marriage. The novelty of this study lies in its integration of Islamic family law with the contemporary phenomenon of digital culture—an intersection that remains underexplored in academic discourse. However, the study is limited by the absence of primary field data such as interviews or direct observation, which constrains a deeper understanding of Gen Z’s personal experiences. Nevertheless, this research contributes to the discourse on reforming Islamic family law to be more responsive and adaptive to the evolving values of the younger generation.